2016
DOI: 10.1016/j.anbehav.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians breeding in refuge habitats have larvae with stronger antipredator responses

Abstract: Antipredator responses are a key determinant of the successful persistence of prey, and behavioural modifications are a frequent antipredator strategy. However, conspecific populations often inhabit heterogeneous environments. This can determine local adaptations, and might also induce variation in antipredator responses. Nevertheless, there is limited information on whether heterogeneity of predation risk among populations determines variation in antipredator response. Here we studied the fire salamander, Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
(64 reference statements)
3
24
0
Order By: Relevance
“…The activity of fire salamander larvae was related to the risk of being preyed and surface streams showed a higher predation risk than caves (Manenti et al 2016). We observed strong differences on the rate of active larvae both between subterranean water and epigean spring pools, as well as during day or night time.…”
Section: Larvae Activity In Caves Published and Original Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The activity of fire salamander larvae was related to the risk of being preyed and surface streams showed a higher predation risk than caves (Manenti et al 2016). We observed strong differences on the rate of active larvae both between subterranean water and epigean spring pools, as well as during day or night time.…”
Section: Larvae Activity In Caves Published and Original Resultsmentioning
confidence: 60%
“…Caves may furnish breeding habitats that are more stable, with a more regular hydroperiod, than epigean streams and creeks, that especially in karst areas may be subjected to strong variation depending on the amount of rainfalls (Barzaghi et al 2017;Culver and Pipan 2014). Moreover, cave pools are usually predator deprived habitats for the fire salamander larvae (Manenti et al 2016) that occupy the top level of the aquatic food web in these habitats (Barzaghi et al 2017). This aspect may also be connected with the possibility of caves to provide superior resources than epigean habitats (Culver and Pipan 2014).…”
Section: General Considerations On Cave Exploitations By the Fire Salmentioning
confidence: 99%
“…Previous studies have shown that salamander occurrence in caves is favored by some cave features, such as the stability of habitat (water permanence), the absence of predators, and the availability of resources [47,48]. Caves and other subterranean environments with groundwater may offer more stable breeding habitats, with a more regular hydroperiod, than surface streams and creeks, which especially in karst landscapes may be subjected to strong variation depending on the amount of rainfalls [26]. Moreover, cave pools are usually predator-deprived environments and can be considered as safe habitats for the fire salamander larvae [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, a growing number of studies has investigated the ecology of fire salamanders (Salamandra salamandra) breeding in underground environments. This species is an ovoviviparous widespread amphibian in Europe that shows high ecological plasticity in the choice of breeding sites [25][26][27]. This salamander can breed in numerous subterranean environments; larvae can be found in natural caves streams and pools, artificial hypogean springs and flooded mines where they may reach high densities [28].…”
Section: Introductionmentioning
confidence: 99%
“…Eyes were markedly red indicating a lack of pigment in the iris. The larva was collected in the context of a three-year long ethological study (Manenti et al, 2013) and reared in controlled conditions (authorization by Lombardy Region, p. n. F12013.0002091; rearing conditions are described in Manenti et al (2016). During the last larval stage the individual developed a number of large yellow dorsal spots (Fig.…”
Section: Resultsmentioning
confidence: 99%